Lugol’s Iodine-Enhanced Micro-CT: A Potential 3-D Imaging Method for Detecting Tongue Squamous Cell Carcinoma Specimens in Surgery - Xia, Cheng-Wan; Gan, Rong-lin; Pan, Jiong-ru; Hu, Shi-qi; Zhou, Qun-zhi; Chen, Shen; Zhang, Lei; Hu, Qin-Gang; Wang, Yu-Xin (Frontiers in Oncology, 2020)
Background A positive surgical margin (PSM) following oral cancer resection results in local recurrence and poor prognosis. Mono-block tumor specimens, especially from the tumor base, are difficult to evaluate. This inaccurate sampling ultimately leads to a false pathological diagnosis. Lugol’s iodine (I2-IK)-enhanced micro-CT is an emerging method to image tumor specimens. This study explores the feasibility of I2-IK-enhanced micro-CT to evaluate the surgical margin for tongue squamous cell carcinoma (TSCC) specimens and to further seek optimal staining parameters. Methods Rabbit tongue tissues and human TSCC samples were imaged via I2-IK-enhanced micro-CT. The optimal I2-IK concentration and staining time were determined before clinical application using tissue shrinkage, micro-CT image quality, and effect on pathological diagnosis as assessment criteria. Next, 6 TSCC specimens were used to verify the process feasibility of surgical margin imaging with the optimal parameters. Finally, the possible reason by which I2-IK could enhance micro-CT imaging was validated in vitro. Results I2-IK staining influenced specimen shrinkage, micro-CT image quality, and pathological image quality in a concentration- and time-dependent manner. After comprehensively considering these indicators, 3% I2-IK staining for 48 and 12 h were found to be optimal for rabbit tongue tissues and TSCC samples, respectively. This method could provide a detailed 3-D structure of TSCC samples compared with H&E sections. Moreover, tumor and normal tissues could be differentiated by their glycogen content, which has high affinity with I2-IK. Conclusions I2-IK-enhanced micro-CT could, thus, indicate the tumor margin and assist pathological sampling in patients with TSCC postoperation.